2007
DOI: 10.1603/0022-2585(2007)44[516:tilaoc]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in Larval Aggregations of Carrion-Feeding Blow Flies (Diptera: Calliphoridae)

Abstract: The growth and development of carrion-feeding calliphorid (Diptera: Calliphoridae) larvae, or maggots, is of great interest to forensic sciences, especially for estimation of a postmortem interval (PMI). The development rate of calliphorid larvae is influenced by the temperature of their immediate environment. Heat generation in larval feeding aggregations (=maggot masses) is a well-known phenomenon, but it has not been quantitatively described. Calculated development rates that do not include internally gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 21 publications
1
61
1
1
Order By: Relevance
“…It may be that ambient temperature is insignificant when a large maggot mass is present. Maggot masses greater than 20 cm 3 exhibit internal temperatures independent of the ambient temperature (24). Thus, an investigation on developmental variation between populations under more natural conditions is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that ambient temperature is insignificant when a large maggot mass is present. Maggot masses greater than 20 cm 3 exhibit internal temperatures independent of the ambient temperature (24). Thus, an investigation on developmental variation between populations under more natural conditions is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that larval population density is related to the increase in heat generated relative to ambient tem-peratures (Marchenko, 2001;Slone & Gruner, 2007). In many studies, the ambient temperatures (e.g., the setpoints of temperature-controlled cabinets) are reported, but the temperatures actually experienced by the growing larvae are neglected (e.g., Byrd & Butler, 1997).…”
Section: Larval Densitiesmentioning
confidence: 99%
“…However, it is expected that larval development remains possible during the cooler months due to the maggot-mass effect in infested carrion in the field. This would maintain high temperatures, overcoming unfavourable weather conditions and extending the breeding season Slone & Gruner, 2007). Indeed, maggot-masses have been observed to still be active when air temperatures are as low as )4°C (Greenberg, 1991).…”
Section: Larval Developmentmentioning
confidence: 99%
“…De plus, le dégagement de chaleur produit par chaque individu conduit à une augmentation de température au centre de la masse pouvant aller jusqu'à une quinzaine de degrés (Deonier 1940, Greenberg 1991, Joy et al 2006, Slone & Gruner 2007. Cette variation de la température entraîne des variations de vitesse de développement entre les individus se trouvant au centre et ceux en périphérie.…”
Section: Résultatsunclassified